2002
DOI: 10.1094/cchem.2002.79.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Dough and Baking Properties of High‐Amylose and Waxy Wheat Flours

Abstract: The dough properties and baking qualities of a novel high‐amylose wheat flour (HAWF) and a waxy wheat flour (WWF) (both Triticum aestivum L.) were investigated by comparing them with common wheat flours. HAWF and WWF had more dietary fiber than Chinese Spring flour (CSF), a nonwaxy wheat flour. Also, HAWF contained larger amounts of lipids and proteins than WWF and CSF. There were significant differences in the amylose and amylopectin contents among all samples tested. Farinograph data showed water absorptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
123
0
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 149 publications
(153 citation statements)
references
References 14 publications
22
123
0
8
Order By: Relevance
“…Yamamori et al (2000) also found that the short chains (DP 6-10) in amylopectin molecules of the high-amylose wheat starch increased, whereas the level of DP 11-25 chains decreased. The high-amylose wheat was also found to have high values of protein, ash, lipid and dietary fiber as compared to the normal wheat (Morita et al 2002). The unique structure and characteristics of starch and flour composition of the highamylose wheat contributed to the new texture and quality of the wheat-base food products such as bread and pasta.…”
Section: Introductionmentioning
confidence: 99%
“…Yamamori et al (2000) also found that the short chains (DP 6-10) in amylopectin molecules of the high-amylose wheat starch increased, whereas the level of DP 11-25 chains decreased. The high-amylose wheat was also found to have high values of protein, ash, lipid and dietary fiber as compared to the normal wheat (Morita et al 2002). The unique structure and characteristics of starch and flour composition of the highamylose wheat contributed to the new texture and quality of the wheat-base food products such as bread and pasta.…”
Section: Introductionmentioning
confidence: 99%
“…Waxy wheat only made poor qualities of bread and noodles (Morita et al 2002b, Baik and Lee 2003, Park and Baik 2004b. Blends of waxy and non-waxy wheat result in high loaf volume and less staling of the breadcrumb (Lee et al 2001, Morita et al 2002a and improved texture of noodles (Guo et al 2003, Baik andLee 2003).…”
mentioning
confidence: 99%
“…The starch of Haruibuki having high amylose content led to the low peak and final viscosities of the paste. Morita et al (2002a) also reported that the high amylose wheat flour had lower gelatinization temperature and maximum viscosity than the waxy and non-waxy wheat flours. In contrast, the lower amylose content of wheat flour showed higher peak and lower final viscosity as reported by Zeng et al (1997).…”
Section: Resultsmentioning
confidence: 93%